Estimating of Sediment Transport Rates for Euphrates River in Al- Hindiya City Using HEC-RAS Model - Hameed, Luay Kadhim (Arab Journal for Sciences and Research Publishing, 2016)
A Hydraulic analysis was performed to estimate sediment transport rates for the Euphrates River at a specified reach in (Al- Hindiya city). Information presented in this study includes surveyed channel cross sections, discharge, stages, and measurements of bed material characteristics. The study reach was between station (Km 625+200) upstream and station (Km 639+200) downstream with a length of (14) km. This reach includes (20) cross sections. HEC-RAS (4.1) package was used and applied for modeling and calculating the sediment transport by (Ackers-white, Engelund-Hansen, Laursen, Toffaleti, and Yang) formulas. Hydraulic computations existing in HEC-RAS4 were used to compute a series of steady flow profiles (13 profiles). These profiles used to develop hydro-dynamic parameters for sediment transport and calibrated to the hydraulic conditions of the reach. A stable solution for sediment transport rates was obtained under specified conditions. The modeling formulas were compared with the field results and the closest formula to the field results was (Laursen), while (Ackers-White) formula was the poor one while the other samples give lower results than the field values with a bit of convergence in some of these results which had been obtained through statistical method. The average annual sediment transport has been predicted by (Laursen) formula using HEC-RAS (4.1) model to be (3376) tons.